Management of Patients with Atopic Dermatitis: The Role of Emollient Therapy - M. Catherine Mack Correa; Judith Nebus (Hindawi Limited, 2012)
Atopic dermatitis is a common inflammatory skin disorder that afflicts a growing number of young children. Genetic, immune, and environmental factors interact in a complex fashion to contribute to disease expression. The compromised stratum corneum found in atopic dermatitis leads to skin barrier dysfunction, which results in aggravation of symptoms by aeroallergens, microbes, and other insults. Infants-whose immune system and epidermal barrier are still developing-display a higher frequency of atopic dermatitis. Management of patients with atopic dermatitis includes maintaining optimal skin care, avoiding allergic triggers, and routinely using emollients to maintain a hydrated stratum corneum and to improve barrier function. Flares of atopic dermatitis are often managed with courses of topical corticosteroids or calcineurin inhibitors. This paper discusses the role of emollients in the management of atopic dermatitis, with particular emphasis on infants and young children.